The monitoring of independent student work with the help of didactic maintenance - Irina N. Pavlova; Natalya V. Spiridonova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In order to improve the efficiency of independent student work a survey of first and second year students of different faculties of SamSTU was conducted. This article discusses and analyzes the results of the survey.